Airports and population density: where benefits outweigh costs. Issue 3 (4th March 2023) - Cattaneo, Mattia; Morlotti, Chiara; Malighetti, Paolo; Redondi, Renato
ABSTRACT: This study investigates the impact of airports on population density distribution in the surrounding areas. Using data for 197 European airports, results show that a 10% increase in airport activity leads to a growth in population density of 3.8%. While moving farther from the city centre leads to a decline in population density, we demonstrate that, on average, population density increases up to 7.5 km from the airport, then starts to decrease beyond that threshold. This threshold can be interpreted as the point in space where positive effects start outweighing negative externalities.